2013
DOI: 10.7860/jcdr/2013/5530.3337
|View full text |Cite
|
Sign up to set email alerts
|

Anti Mullerian Hormone: A Potential Marker for Recruited Non Growing Follicle of Ovarian Pool in Women with Polycystic Ovarian Syndrome

Abstract: Background: Polycystic ovarian disease is one of the most common causes of infertility in women of reproductive age. Anti-mullerian hormone (AMH), a member of transforming growth factor (TGF) family which is secreted by granulosa cells of growing follicle, is found to be increased to three to four fold in Poly Cystic Ovarian Syndrome (PCOS) patients as evidenced by previous studies. But the level of AMH in relation to the infertile status of PCOS was not studied yet. The present study was focused to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
3
12
1
1
Order By: Relevance
“…26,29,30 In our study, 100.00% sensitivity and 95.83% specificity were seen with a cutoff value of 3.6 ( Table 4) which is similar to another study from India (3.34 ng/mL). 30 AMH has been assessed for diagnosis of PCOS with reference to the major classifications of PCOS. 26,31 Eilertsen et al 31 concluded that AMH could successfully replace PCOM for the diagnosis of PCOS and that substitution of AMH with PCOM was equally effective for diagnosis in both the AES (Androgen Excess Society) and Rotterdam criteria an opinion that was supported by Sahmay S et al 26 Thus, in the hormonal workup of persistent acne in females, AMH may be used as a parameter to diagnose PCOM and is superior to testing for androgens and gonadotropins (K€ oninger A et al).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…26,29,30 In our study, 100.00% sensitivity and 95.83% specificity were seen with a cutoff value of 3.6 ( Table 4) which is similar to another study from India (3.34 ng/mL). 30 AMH has been assessed for diagnosis of PCOS with reference to the major classifications of PCOS. 26,31 Eilertsen et al 31 concluded that AMH could successfully replace PCOM for the diagnosis of PCOS and that substitution of AMH with PCOM was equally effective for diagnosis in both the AES (Androgen Excess Society) and Rotterdam criteria an opinion that was supported by Sahmay S et al 26 Thus, in the hormonal workup of persistent acne in females, AMH may be used as a parameter to diagnose PCOM and is superior to testing for androgens and gonadotropins (K€ oninger A et al).…”
Section: Discussionsupporting
confidence: 89%
“…33 Various studies have found a high sensitivity and specificity of AMH in the diagnosis of PCOS with a cutoff value ranging from 3.34 to 4.7 ng/mL. 26,29,30 In our study, 100.00% sensitivity and 95.83% specificity were seen with a cutoff value of 3.6 ( Table 4) which is similar to another study from India (3.34 ng/mL). 30 AMH has been assessed for diagnosis of PCOS with reference to the major classifications of PCOS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Of these genes, the JUN and fra-1 mediated cell cycle pathway; SMAD3 and SMAD4 were downstream of TGF-β, which was found to be increased by 3–4 fold in PCOS. This its dysregulation may contribute to ( 1 ) the fetal origins of PCOS, ( 2 ) reproductive abnormalities in PCOS and ( 4 ) cardiovascular and metabolic abnormalities in PCOS ( 28 , 37 ), suggesting JUN-associated pathways may be important in PCOS.…”
Section: Discussionmentioning
confidence: 99%